Effects of infection control measures towards preventing SARS-CoV-2 outbreaks in a German choir boarding school from March 2020 to April 2022 - Lampl, Benedikt M. J.; Schöberl, Patricia; Atzenbeck, Noah; Erdl, Michael; Dillitzer, Nepomuk; Wallbrecher, Jakov; Weigl, Marcus; Sauer, Michael; Kheiroddin, Parastoo; Niggel, Jakob; Mauerer, Richard; Ambrosch, Andreas; et al. (Frontiers in Pediatrics, 2023)
Background: Singing in a choir was associated with larger outbreaks in the beginning of the SARS-CoV-2 pandemic.We report on the effect and acceptance of various infection control measures on the occurrence of SARS-CoV-2 infections in the world famous Domspatzen boys' choir from September 2020 to April 2022.In addition to basic general hygiene measures, systematic rRT-PCR testing and scientifically approved concepts of distancing during singing were applied. While single infections of choir members could not be avoided, singing-related outbreaks were not observed. Until the Omicron variant emerged, potential transmission of SARS-CoV-2 in the school was limited to only one case. Incidences at the school were never higher than in the comparable general population until then. While the impact of the pandemic on daily life and singing was rated as severe, especially by staff members, most students agreed with the usefulness of protection measures and rated them as acceptable. Students viewed regular testing as the most important tool to increase safety in the school.Discussion: A bundle of infection control measures including regular testing can prevent outbreaks of SARS-CoV-2 even in the setting of choir singing. Measures are acceptable for choir members if they allow to continue with singing and performing.